7/12 -1/3
7/12-4/12=3/12
3/12/ (3/4)= 3/12* 4/3= 12/36= 1/3
2007-01-07 16:35:19
·
answer #1
·
answered by shadouse 6
·
1⤊
0⤋
The way I read the question I made the following formual
7/12 - (1/3 x 3/4)
7/12 - 3/12
4/12 = 1/3
now looking at the question again I see:
1/3 - 7/12 divided by 3/4
or is it 7/12 - 1/3 divided by 3/4
we shall have to find out which is greater 1/3 or 7/12
1/3 7/12
1/3 = 4/12
therefore it must be 7/12 - 4/12 = 3/12
3/12 divided by 3/4 = 3/12 x 4/3 = 3/9 = 1/3
so it is the same answer both ways
2007-01-08 10:37:37
·
answer #2
·
answered by David C 2
·
0⤊
0⤋
3/4 / (7/12 - 1/3) = 3/4 / 1 / 4 = 3
2007-01-08 00:59:10
·
answer #3
·
answered by James Chan 4
·
0⤊
0⤋
7/12-4/12 = 3/12
1/4 divide by 3/4 = 1/4 x 4/3 = 4/12 = 1/3
2007-01-08 00:41:47
·
answer #4
·
answered by B T 3
·
0⤊
0⤋
if im reading your question right, which i think i am...
[ ( 7 / 12 ) - ( 1 / 3 ) ] / ( 3 / 4 )
so you need a common denominator for the first part so (1/3) = (4/12), the equation is now
[ ( 7 / 12 ) - ( 4 / 12 ) ] / ( 3 / 4 )
do the subtraction and get
(3/12) / (3/4)
reduce (3/12) to (1/4) to get
(1/4) / (3/4)
to divide by a fraction is to multiply by the reciprocol so you have
(1/4) * (4/3) and this gives...
(4/12)
reduce this to your answer of
(1/3)
and you are done
2007-01-08 00:39:42
·
answer #5
·
answered by smartguy_1457 2
·
0⤊
0⤋
(7/12 - 1/3)/(3/4) =
(4/3)(7/12 - 4/12) =
(4/3)(3/12) =
(3/3)(4/12) =
1/3
2007-01-08 00:50:55
·
answer #6
·
answered by Helmut 7
·
0⤊
0⤋
Just make them numbers:
((7/12) - (1/3)) / (3/4)
Then make them all have the same denominator(12):
((7/12-(4/12))/(9/12)
Then subtract
(3/12) / (9/12)
Now then multiply 3/12 by 12/9 since you divided by 9/12
(3/12) * (12/9) = 3/9 =[1/3]
2007-01-08 00:35:30
·
answer #7
·
answered by TheThing 2
·
0⤊
0⤋
7/12 - 1/3 = 9/36 = 1/4
(1/4) / (3/4) is same as (1/4*4) / 3 = 1/3
2007-01-08 00:51:46
·
answer #8
·
answered by Sammy 2
·
0⤊
0⤋
Repeat after me. "Math is not magic. It makes perfect sense. All I have to do is right the problem down correctly and follow the rules to solve the problem."
Okay, so I'll get you started the difference of 7/12 and 1/3 is the the same as saying (7/12) - (1/3) Now stop being afraid of math and work.
2007-01-08 00:36:35
·
answer #9
·
answered by Jacob P 2
·
0⤊
0⤋
[(7/12) - (4/12)] * (4/3) = (1/4)(4/3) = (1/3).
2007-01-08 00:38:57
·
answer #10
·
answered by S. B. 6
·
0⤊
0⤋